Using social audits to improve delivery of state nutrition-related services: Lessons from the CAN Program - Gordon, Jessica; Tranchant, Jean-Pierre; Nisbett, Nicholas (International Food Policy Research Institute, 2020)
The overall goal of the three-year CAN program (2016–2019) was “Reducing malnutrition among children and women by facilitating efficient implementation of food and nutrition programmes, ensuring transparency, downward accountability and community participation.” The main intervention was a social audit process designed to sensitize communities to their rights and entitlements under the four primary schemes under the NFSA. The program aimed to increase knowledge and uptake of NFSA services, improve participation in community-level governance activities, especially by women, and improve institutional delivery of nutrition services and entitlements, as well as to reduce malnutrition, especially among women and children. Combining quantitative, qualitative, and process methodologies, the IDS-led evaluation looked at immediate impacts on strengthening local governance and improving service in the ICDS, Mamata, and TPDS programs, and explored contextual, design, and implementation-related factors that may have affected the effectiveness of the social audits. Communities (GPs) selected by the SPREAD program were randomly split into an Early and a Late group, which went through the audit process at different times. The quantitative analysis used differences in outcomes between groups to try to understand how change happened, how it accumulated, and whether it might be short-lived—important considerations for complex village-level governance.